Management of acute renal failure - Gavrilovska-Brzanov Aleksandra (epartment of Anesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2020)
In multiple clinical settings, Acute Kidney Injury (AKI) is a frequent condition. AKI increases the short and long-term mortality rate. Although the condition has become more widely recognized, yet there is still lack of definitions and increased number of studies has appeared examining AKI across many different clinical settings. Detailed medical history and physical examination are the key in determining the etiology of AKI and timeline of the progress. The fundamental principles in management of AKI are to treat the underlying cause, optimizing fluid balance and hemodynamics, correct electrolytes and eliminate or adjust the dose of nephrotoxic drugs. Therefore, optimizing hemodynamics and correction of volume depletion will minimize continuation of kidney injury and will improve recovery, preventing any chronic impairment of the kidney. However, there are no guidelines for improving hemodynamics and optimizing volume status for kidney protection. International guidelines for management of sepsis and septic shock recommend a goal-directed therapy (GDT). Acute Dialysis Quality Initiative has proposed a new fluid resuscitation strategy consisting of four phases: rescue, optimization, stabilization and de-escalation phases. Liberal fluid administration is allowed in the rescue phase; in the optimization phase, where the patient is hemodynamically stable, percutaneous fluid management is required with the aim to maintain hemodynamic stability; in the stabilization phase, when the patient is stable, equal or negative fluid balance is preferred; and in last de-escalation phase, all excessive fluid should be removed.
Keywords: acute kidney injury; acute kidney injury management; acute renal failure